Effects of elevated air temperatures on soil thermal and hydrologic processes in the active layer in an alpine meadow ecosystem of the Qinghai-Tibet Plateau - Bai Wei; Wang Genxu; Liu Guangsheng (Journal of Mountain Science, 2012)
In this study, effects of elevated air temperatures on thermal and hydrologic process of the shallow soil in the active layer were investigated. Open-top chambers (OTCs) were utilized to increase air temperatures 1-2A degrees C in OTC-1 and 3-5A degrees C in OTC-2 in the alpine meadow ecosystem on the Qinghai-Tibetan Plateau. Results show that the annual air temperatures under OTC-1 and OTC-2 were 1.21A degrees C and 3.62A degrees C higher than the Control, respectively. The entirely-frozen period of shallow soil in the active layer was shortened and the fully thawed period was prolonged with temperature increase. The maximum penetration depth and duration of the negative isotherm during the entirely-frozen period decreased, and soil freezing was retarded in the local scope of the soil profile when temperature increased. Meanwhile, the positive isotherm during the fully-thawed period increased, and the soil thawing was accelerated. Soil moisture under different manipulations decreased with the temperature increase at the same depth. During the early freezing period and the early fullythawed period, the maximum soil moisture under the Control manipulation was at 0.2 m deep, whereas under OTC-1 and OTC-2 manipulations, the maximum soil moisture were at 0.4-0.5 m deep. These results indicate that elevated temperatures led to a decrease of the moisture in the surface soil. The coupled relationship between soil temperature and moisture was significantly affected by the temperature increase. During the freezing and thawing processes, the soil temperature and moisture under different manipulations fit the regression model given by the equation theta (V)=a/{;1+exp[b(TS+c)]}+d.